Penggunaaan bahan alami briket arang kayu sebagai penyerap dan penyimpan kalor solar still desalinasi interfasial - Jafri, Muhamad; Alfarisi, Figo Jafri; Tarigan, Ben Vasco (Universitas Nusa Cendana, 2024)
Considering that solar energy is unlimited, it is hoped that the solar still distillation method can be used in remote and poor areas without pollution and excessive consumption of fossil fuel materials. In this research, charcoal from dried Kusambi (Schleichera Oleosa) coded SO_W is used as a carbon-based heat absorbing and storing material, which has porous characteristics and high energy absorption so that it forms a wider surface for radiation and convection. The experiment was carried out in 4 basins using Styrofoam containing charcoal briquettes with a cross-section of 4, 6, and 8 sections with different sizes and areas in 1 absorber section for 8 hours under sunlight. Basins without charcoal were also tested as a comparison. Temperature is measured at several points in the basin to identify factors influencing evaporation. The results of the research show that adding heat-absorbing material to the basin can accelerate seawater to reach its boiling point so that it can evaporate (evaporation). Temperature and humidity in each basin also have similar changing trends where temperature is strongly influenced by solar radiation. The use of charcoal briquettes can also increase the rate of convection and evaporation heat transfer in the basin, as well as maximum efficiency in basin 2 with a variation of 6 plots of 39.97%, followed by a variation of 4 plots in basin 1 of 38.32%, and a variation of 8 plots in basin 3 it was 37.59%. Meanwhile, in basin 4 with the variation without charcoal, the efficiency was 34.96%.